2010
DOI: 10.2337/dc09-1229
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Perceived Diabetes Control Are Not Related to Actual Glucose Control for Minority Patients With Diabetes

Abstract: OBJECTIVETo examine variables associated with perceived diabetes control compared with an objective measure of glucose control (A1C).RESEARCH DESIGN AND METHODSBeliefs about diabetes were assessed among 334 individuals with diabetes living in a primarily low-income, minority, urban neighborhood. Regression analyses tested associations between disease beliefs and both participants' perceptions of control and actual control (A1C).RESULTSPoorer perceived diabetes control was associated with perceiving a greater i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
2
13
1
Order By: Relevance
“…Rather, we found that HbA1C was associated with dietary appraisal. These results are consistent with the conclusion reached by McAndrew et al (2010), who stated that perceived control is not always congruent with actual glucose control in minority patients with diabetes in the United States. This indicates the importance of differentiating between dietary appraisal and perceived control when dealing with mutually close constructs of control.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Rather, we found that HbA1C was associated with dietary appraisal. These results are consistent with the conclusion reached by McAndrew et al (2010), who stated that perceived control is not always congruent with actual glucose control in minority patients with diabetes in the United States. This indicates the importance of differentiating between dietary appraisal and perceived control when dealing with mutually close constructs of control.…”
Section: Discussionsupporting
confidence: 91%
“…In this study none of the possible confounders reported in previous research (De Ridder et al, 2007;Hampson et al, 1990;Lange and Piette, 2006;Lawson et al, 2007;McAndrew et al, 2010;Skinner and Hampson, 1998;Skinner et al, 2000) were associated with perceived control. Rather, we found that HbA1C was associated with dietary appraisal.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations